2023
DOI: 10.1029/2022jg006954
|View full text |Cite
|
Sign up to set email alerts
|

River Corridor Sources Dominate CO2 Emissions From a Lowland River Network

Abstract: Rivers and streams are control points for CO2 emission to the air (fCO2), with emission rates often exceeding internal metabolism (net ecosystem production, NEP). The difference is usually attributed to CO2‐supersaturated groundwater inputs from upland soil respiration and rock weathering, but this implies a terrestrial‐to‐aquatic C transfer greater than estimated by terrestrial mass balance. One explanation is that riparian zones—rich in organic and inorganic C but mostly neglected in terrestrial mass balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…The relationships between land cover and median CO 2 concentration and emission rates also follow previous studies (Borges et al 2018), where the importance of certain sources of CO 2 to streams and the production of CO 2 within the stream are influenced by land cover (Marescaux et al 2018). For example, wetlands can provide a large supply of CO 2 to lotic ecosystems (Abril et al 2014; Kirk and Cohen 2023), where CO 2 produced in wetlands is transported to streams and emitted there. Similarly, urbanization has been shown to increase riverine CO 2 emissions (Gu et al 2021; Zhang et al 2021), where increased inputs of nutrients and organic matter fuel in‐stream production of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between land cover and median CO 2 concentration and emission rates also follow previous studies (Borges et al 2018), where the importance of certain sources of CO 2 to streams and the production of CO 2 within the stream are influenced by land cover (Marescaux et al 2018). For example, wetlands can provide a large supply of CO 2 to lotic ecosystems (Abril et al 2014; Kirk and Cohen 2023), where CO 2 produced in wetlands is transported to streams and emitted there. Similarly, urbanization has been shown to increase riverine CO 2 emissions (Gu et al 2021; Zhang et al 2021), where increased inputs of nutrients and organic matter fuel in‐stream production of CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to expect that these findings from northern regions would also apply to tropical streams. Recently Kirk and Cohen (2023) found that despite their modest spatial extent, riparian corridors supplied up to 49% of the CO 2 outgassing from a subtropical stream in Florida. While our study did not provide a conclusive answer on the role of the riparian corridor in fueling the stream C pool, indirect evidence suggests that it acted as a major source of C to Manton Creek.…”
Section: Riparian Corridors As An Overlooked C Sourcementioning
confidence: 99%
“…Despite their importance in the terrestrial carbon cycle, the relative balance of CO 2 sources that support carbon fluxes to the atmosphere, which include groundwater sources such as soil respiration and subsurface chemical weathering reactions, or stream corridor sources including respiration of organic matter within the hyporheic zone and water‐column as balanced by photosynthesis, remains uncertain. More recently, studies have shown the potential role of carbonate buffering reactions to contribute to evasing fluxes and spatial patterns of stream CO 2 partial pressure ( p CO 2 ) (Duvert et al., 2019; Kirk & Cohen, 2023; Stets et al., 2017; Wang et al., 2021). Crucially, these buffering dynamics are not typically included in freshwater system carbon budgets and may represent an overlooked aspect of terrestrial‐aquatic carbon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Stets et al (2017) suggest that this effect is responsible for the observations of high downstream pCO 2 in high alkalinity streams despite significant degassing during downstream transport. These buffering reactions may also contribute significantly to total stream emissions (e.g., Kirk & Cohen, 2023); for example, Duvert et al (2019) found that up to 60% of emissions were supported by carbonate buffering at some locations within a high alkalinity, tropical Australian river system.…”
mentioning
confidence: 99%